2005
DOI: 10.1371/journal.pgen.0030033.eor
|View full text |Cite|
|
Sign up to set email alerts
|

Inducible and Reversible Clock Gene Expression in Brain Using the tTA System for the Study of Circadian Behavior

Abstract: The mechanism of circadian oscillations in mammals is cell autonomous and is generated by a set of genes that form a transcriptional autoregulatory feedback loop. While these ''clock genes'' are well conserved among animals, their specific functions remain to be fully understood and their roles in central versus peripheral circadian oscillators remain to be defined. We utilized the in vivo inducible tetracycline-controlled transactivator (tTA) system to regulate Clock gene expression conditionally in a tissue-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 89 publications
(150 reference statements)
1
19
0
1
Order By: Relevance
“…Hong et al (50) reported that high doses of doxycycline can lead to prolonged suppression of Cre expression even after withdrawal of doxycycline, whereas lower doses of doxycycline allow improved titration of Cre expression. We therefore tested doxycycline at a 200-fold lower dose (10 g/ml) in drinking water starting from conception.…”
Section: Resultsmentioning
confidence: 99%
“…Hong et al (50) reported that high doses of doxycycline can lead to prolonged suppression of Cre expression even after withdrawal of doxycycline, whereas lower doses of doxycycline allow improved titration of Cre expression. We therefore tested doxycycline at a 200-fold lower dose (10 g/ml) in drinking water starting from conception.…”
Section: Resultsmentioning
confidence: 99%
“…As with fibroblasts (19), a 2-h serum shock was able to synchronize the molecular clock in the Y1 cells. The serum shock caused rhythmic steroid production and cyclic StAR mRNA accumulation with Ϸ24-h periodicity that persisted for up to 60 h. These features clearly depended on an intact cellular clock, because overexpression of CLOCK⌬19, a defective mutant of CLOCK (20), dampened the cyclic profiles of both steroid production and StAR mRNA expression ( Fig. 2 A and B).…”
Section: Circadian Rhythms Of Cs Production and Adrenal Steroidogenicmentioning
confidence: 91%
“…Assessing cardiovascular parameters throughout the circadian day in transgenic mouse models with disrupted circadian clocks has provided initial information in this regard. 48,50 However, forthcoming studies of mouse models with tissue restricted dysfunctional molecular clocks 51,52 will allow a greater understanding of the relative contribution of both systemic cues and these peripheral oscillators to physiology and disease.…”
Section: Circadian Gene Expression In the Vasculaturementioning
confidence: 99%